Strategi pengembangan agribisnis sagu di Kecamatan Patani Utara Kabupaten Halmahera Tengah - Bahmid, Wahyono; Saleh, Erna Rusliana M; Hartati, Tri Mulya (Jurnal Pertanian Khairun, 2024)
Sago has the ability to significantly boost the Central Halmahera Regency's North Patani District local economy. Strategies that promote raising the economic value of sago starch products must be developed in order to guarantee that this potential is sustained. The purpose of this study is to use the Process Hierarchy Analysis Method (AHP) to identify alternative decision priorities. This approach include gathering information via field surveys, literature reviews, and expert and pertinent stakeholder interviews. The research's conclusions offer tactical recommendations for enhancing the region's sago agribusiness's sustainability, marketing, and production. The use of contemporary processing technology is the factor with the highest priority, according to the analysis. From peeling to drying, the goal is to make every step of the sago manufacturing process more efficient. In addition, institutional planning is seen as a high priority. Increasing productivity, efficiency, and added value in the manufacturing and marketing of sago products is the main goal of this strategy. It is envisaged that by putting these techniques into practice, farmers' incomes will rise and sago products' market access will expand. The community's economic well-being in North Patani District, Central Halmahera Regency, is anticipated to significantly improve as a result of this change.Keywords: development strategy, sago agribusiness, AHP method